A Cross-Linguistic, Longitudinal Study of the Foundations of Decoding and Reading Comprehension Ability. (3rd September 2019) - Caravolas, Markéta; Lervåg, Arne; Mikulajová, Marína; Defior, Sylvia; Seidlová-Málková, Gabriela; Hulme, Charles
ABSTRACT: The present study investigated the moderating role of orthographic consistency on the development of reading comprehension in four language groups (English, n  = 179; Spanish, n  = 188; Czech, n  = 135; Slovak, n  = 194) from kindergarten to Grade 2. In all languages, early variations in phoneme awareness/letter knowledge, rapid automatised naming, and emerging decoding skills, but not oral language, predicted variations in decoding skills at the end of Grade 1; these in turn predicted reading comprehension in Grade 2. For the three consistent orthographies (Spanish, Slovak, and Czech), kindergarten language skills were another significant predictor of Grade 2 reading comprehension. This effect was absent in the English sample, where variations in decoding skills were a more powerful predictor. These results provide the first longitudinal evidence for effects of orthographic consistency on the development of reading comprehension and provide support for the simple view of reading.